Philippine Minor Languages and Language Planning - Sibayan, Bonifacio P. (The Archive, 2025)
It is a pleasure and a privilege to talk before you today to discuss the subject of Philippine minor languages and language planning (LP). I am specially pleased to have been invited because of my being considered a son of Kankana-ey speaking peoples. I am proud of my minority language background. It has made my life richer. I look back with a great deal of happiness to the mountain provinces and the people who speak their minor languages. When we speak of minor languages (ML), I suggest that the focus be on the people who speak them. Such a concern for minor languages is a manifestation of our concern for the people who speak them. This will give us the proper perspective or at least a much better view when we talk of LP involving minor Philippine languages. It is appropriate that the theme of this Congress is the Philippine minor languages and the Filipino.